Tribological properties of highly oriented Ti(C, N) deposited by chemical vapor deposition. (March 2018) - von Fieandt, L.; Fallqvist, M.; Larsson, T.; Lindahl, E.; Boman, M.
Abstract: Two Ti(C, N) coatings were tested by means of micro abrasion and scratch testing. The coatings differed in grain size, orientation (<111> and <111>, <311> and <211> respectively) and hardness (36 GPa and 23 GPa respectively). The <111> oriented coating had a 20% higher wear resistance compared to the reference coating when abraded with 1 μm diamonds. When abraded with 6 μm diamonds the abrasion resistance of the reference coating was superior compared to the <111> oriented coating by 36%. Furthermore, it was found that the <111> oriented coating had 35% better adhesion compared to the reference. The improved mechanical properties of the <111> oriented coating was attributed to a high degree of orientation and the higher hardness. Highlights: Superior abrasion resistance for <111> oriented Ti(C, N) using 1 μm diamond abrasive. <111> oriented Ti(C, N) has superior adhesion compared to <211> oriented Ti(C, N). <111> oriented Ti(C, N) has higher crack resistance than <211> oriented Ti(C, N).